2005
DOI: 10.1002/bem.20177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsed magnetic stimulation on tumor development and immune functions in mice

Abstract: We investigated the effects of pulsed magnetic stimulation on tumor development processes and immune functions in mice. A circular coil (inner diameter = 15 mm, outer diameter = 75 mm) was used in the experiments. Stimulus conditions were pulse width = 238 micros, peak magnetic field = 0.25 T (at the center of the coil), frequency = 25 pulses/s, 1,000 pulses/sample/day and magnetically induced eddy currents in mice = 0.79-1.54 A/m(2). In an animal study, B16-BL6 melanoma model mice were exposed to the pulsed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 39 publications
(43 reference statements)
1
47
0
1
Order By: Relevance
“…Electrical stimulation is well known to cause changes in the local pH and/or temperature, which can lead to cell death. 37,38 However, the eddy currents generated in our study induced change in neither pH nor temperature (2.66×10 -10 9 C/ pulse). 37 We also tested the eŠects of IM and MS on IM-resistant BCR/ABL (+) cells to examine what cellular mechanisms were involved.…”
Section: Recent Medical Applications That Use Electromagnetic Fieldsmentioning
confidence: 56%
See 1 more Smart Citation
“…Electrical stimulation is well known to cause changes in the local pH and/or temperature, which can lead to cell death. 37,38 However, the eddy currents generated in our study induced change in neither pH nor temperature (2.66×10 -10 9 C/ pulse). 37 We also tested the eŠects of IM and MS on IM-resistant BCR/ABL (+) cells to examine what cellular mechanisms were involved.…”
Section: Recent Medical Applications That Use Electromagnetic Fieldsmentioning
confidence: 56%
“…22,23 Our group has demonstrated the enhanced killing e‹ciency of imatinib mesylate (IM, Gleevec } , Novartis, East Hanover, NJ, USA) in human breakpoint cluster region-abelson (BCR/ABL) (+) leukemia cells when the cells were subsequently exposed to MS. 34 BCR/ABL is a chimeric gene, generated by the Philadelphia (Ph) chromosome translocation, t(9;22)(q34;q11), 35 and IM was developed as a potent and speciˆc inhibitor of the BCR/ABL tyrosine kinase. 36,37 Figure 3 shows the system used to expose cells to MS; the stimulus conditions tested were 25 pulses/s and 0.1T (1000 pulses/day), 0.25T (1000 or 6000 pulses/day), or 0.5T (1000 pulses/ day). Using theˆnite method, 38 we calculated the magnetic ‰ux as 0.11 to 0.18T and eddy current as 26.8 to 38.1 A/m 2 as in the culture medium for 0.25T (Fig.…”
Section: Recent Medical Applications That Use Electromagnetic Fieldsmentioning
confidence: 99%
“…There is data supporting the opinion that the use of EMFs has effects in the cell proliferation and in malignant tumours in animals (Tofani et al, 2001;Yamaguchi et al, 2006). It has also been reported that EMFs could act synergistically with chemotherapeutic agents (Gray et al, 2000;Ruiz Gómez et al, 2002), and reverse the resistance of cancer cells in chemotherapy (Hirata et al, 2001;Janigro et al, 2006).…”
mentioning
confidence: 87%
“…Exposure of mice in pulsed magnetic fields lasted 16 days. The experimental data showed anticancer and immunomodulatory properties of pulsed magnetic stimulation such as decrease of tumour growth and elevated production of tumour necrosis factor (TNF-a) in mouse spleens (Yamaguchi et al, 2006). In addition, extremely low-frequency pulsed-gradient magnetic field (with the maximum intensity of 0.6-2.0 T, gradient of 10-100 T/m, pulse width of 20-200 ms and frequency of 0.16-1.34 Hz) presented antitumour and antiangiogenic properties, in exposed Kunming mice bearing murine tumour (Zhang et al, 2002).…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation